Modulation and Modeling of Three‐Dimensional Nanowire Assemblies Targeting Gas Sensors with High Response and Reliability. (27th October 2021) - Han, Hyeuk Jin; Lee, Gyu Rac; Han, Yujin; Jang, Hanhwi; Cho, Eugene N.; Kim, Sunho; Kim, Chang Sub; Yim, Soonmin; Jeong, Jae Won; Kim, Jong Min; Yu, Seunghee; Tuller, Harry L.; et al.
Abstract: Despite improved sensitivity, simple downsizing of gas‐sensing components to randomly arranged nanostructures often faces challenges associated with unpredictable electrical conduction pathways. In the present study, controlled fabrication of three‐dimensional (3D) metal oxide nanowire networks is demonstrated that can greatly improve both signal stability and sensor response compared to random nanowire arrays. For example, the highest ever reported H2 S gas response value, and a 5 times lower relative standard deviation of baseline resistance than that of random nanowires assemblies, are achieved with the ordered 3D nanowire network. Systematic engineering of 3D geometries and their modeling, utilizing equivalent circuit components, provide additional insights into the electrical conduction and gas‐sensing response of 3D assemblies, revealing the critical importance of wire‐to‐wire junction points and their arrangement. These findings suggest new design rules for both enhanced performance and reliability of chemical sensors, which may also be extended to other devices based on nanoscale building blocks. Abstract : Simple downsizing of nano‐building blocks and their assembly typically exhibits a large device‐to‐device variation in gas sensor performance due to unpredictable electrical conduction pathways. This study demonstrates systemically controlled 3D nanostructures can achieve both high sensing response and reproducibility. Combining electrical characterization with equivalent circuit modeling provides important insights into the electrical conduction in 3D assemblies and their gas‐sensing mechanism.